Amide functionalized aminobisphenolato MoO2 and WO2 complexes: Synthesis, characterization, and alkene epoxidation catalysis - Salonen Pasi; Schachner Jörg A.; Peuronen Anssi; Lahtinen Manu; Belaj Ferdinand; Mösch-Zanetti Nadia C.; Lehtonen Ari (Elsevier B.V., 2025)
The use of dioxidomolybdenum(vi) and -tungsten(vi) complexes supported by a variety of structurally different tri- and tetradentate aminobisphenolato ligands as pre-catalysts in the epoxidation of alkenes is well established. However, under the widely used standard 1 mol-% catalyst loadings these types of complexes generally show modest activity only. Recently, amide functionalities in the ligand design of various aminomonophenolato MoO2 complexes have been shown to lead to heightened catalytic activity in alkene epoxidation. In this paper we show that similar ligand amide functionalization can lead to significant enhancement in the alkene epoxidation activity of aminobisphenolato MoO2 complexes. Although the W variants showed much lower performance in comparison, the epoxidation activity of the Mo congeners is generally ca. two orders of magnitude higher than previously reported for structurally related aminobisphenolato complexes. An interesting phenomenon dubbed as “dilution effect” was discovered, wherein pre-catalyst loadings as low as 0.01 mol-% may be realized without significantly reduced impact in activity. Moreover, the [pre-catalyst]:[oxidant] molar ratio – an often overlooked reaction parameter in the literature – was found to be critical for optimal catalytic performance.